The Effect of Elevons Deflection to Aerodynamic Coefficients of A Tail-less Blended Wing-Body Planform / Rizal E. M. Nasir ...[et al.] - M. Nasir, Rizal E.; Basri, Ilyas H.; M. Ahmad, Aiman; A. Latif, Zulfazli A.; Wisnoe, Wirachman; Kuntjoro, Wahyu (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2017)
Control surfaces play a big role in stabilizing and maneuvering an aircraft. This paper investigates the effect of control surface allocations, specifically deflection of four elevons on a BWB planform, on aerodynamic coefficients. Elevon allocations can be in a form of single-elevon deflection, two-elevon deflection in unison or in opposite deflection angles and four-elevon deflections in unison or in opposite deflection angles. Six aerodynamic coefficients which represent three forces and three moments in three axes are measured via wind tunnel experiment at 25 m/s. The wind tunnel model is of a flat, thin plate with planform similar to a typical stealth, flying-wing aircraft. Thirty-one (31) cases of different elevon deflections are tested at a fixed pitch angle of attack and zero angle of sideslip. The results shows that significant changes in drag, sideforce and lift forces are observed at almost all elevon deflection cases. The roll moment and pitch moment change with respect to elevon angle depends on the number of elevons utilized while yaw moment is not much affected by elevon deflections except for some cases.